Mentalizing the patient–Patient experiences with short-term mentalization-based therapy for borderline personality disorder: A qualitative study - Hestbæk, Emilie; Hasselby-Andersen, Mathilde; Juul, Sophie; Beier, Nynne; Simonsen, Sebastian (Frontiers in Psychiatry, 2022)
Background Mentalization-based therapy (MBT) is an evidence-supported psychotherapy approach for borderline personality disorder (BPD) that has been implemented in mental health services worldwide. Originally, MBT was developed as an 18-months program for BPD. However, a short-term (5 months) MBT program has been developed. Research into patient experiences with long-term MBT for BPD is scarce, and no studies have investigated patient experience with short-term MBT for BPD. Objective The objective of this study was to explore patient experience with short-term MBT for BPD in the Danish mental health services. Methods Semi-structured qualitative interviews were conducted with 12 outpatients diagnosed with BPD, who attended short-term MBT for 5 months. The interviews were verbatim transcribed and analyzed using thematic analysis with double coding. Results The analysis resulted in four subordinate themes: (1) Treatment duration – too short or appropriately short?, (2) The group as a “safe space,” (3) Bad experiences impacted treatment negatively, and (4) My life has changed for the better. Conclusion The results suggest that most of the patients were overall satisfied with short-term MBT, which they experienced as having a positive impact on their lives. However, a subgroup of patients wanted more therapy. This study highlighted the strengths and limitations of short-term MBT for BPD as experienced by the patients, and points to barriers in developing service-user informed short-term treatment options for BPD.